Strategies of Improvement of Access to Quality Primary Healthcare in the United Arab Emirates: Lessons to Learn - Doaa Jameel Al-Ramlawi (Faculty of Medicine Universitas Sebelas Maret, 2023)
Introduction: This research topic explores the current state of access to quality primary healthcare in the United Arab Emirates (UAE). It examines the challenges that limit access to quality primary healthcare, such as inadequate infrastructure, limited resources, and a lack of public awareness. It proposes strategies to improve access to quality primary healthcare in the UAE, such as increasing public awareness campaigns, improving infrastructure and resources, and introducing new policies and regulations. It also recommends creating cutting-edge healthcare delivery strategies, such as telemedicine and mobile health technologies. The absence of evidence-based research that concentrates on the efficacy of certain interventions is a problem in the UAE when it comes to developing and improving access to high-quality primary healthcare.Methods: The study employs a qualitative approach to enhance access to quality primary healthcare in the UAE. It employs a descriptive survey for secondary data collection, incorporating and various sources such as reports and online documents.Results: The Health Authority Abu Dhabi has undertaken a research study to evaluate the relationship between regulatory approaches and adherence to regulatory requirements, which will improve healthcare quality.Conclusion: Research on primary healthcare accessibility in the UAE highlights areas for improvement like addressing service gaps and refining care methods. Current shortcomings involve infrastructure and financial constraints, requiring more investment and collaboration. It emphasizes approaches like raising awareness and providing incentives. Involving stakeholders helps ensure access to high-quality healthcare by evidence-based policy recommendations.